2010
DOI: 10.1227/neu.0b013e3181efbb08
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver and Interobserver Agreement in Volumetric Assessment of Glioblastoma Multiforme Resection

Abstract: Postoperative assessment of GBM volume seems to offer high intraobserver agreement, but low interobserver agreement. Using absolute RTV values to relate extent of tumor resection with survival may be unreliable. More research is needed before this method can be used as a valid end point for clinical studies. Computer-assisted tumor volume calculation may increase interobserver agreement in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 17 publications
3
48
2
1
Order By: Relevance
“…No significant difference exists in progression-free survival, and most importantly: There is a lack of a valid methodology for volumetric assessment of glioblastoma resection. [61323] In our opinion, tumor volumes reported in the study of Senft are within the error limits of tumor volumetry. Further, a clear definition of “tumor” is one of the challenges to be solved besides improving accuracy of glioblastoma volumetry itself.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…No significant difference exists in progression-free survival, and most importantly: There is a lack of a valid methodology for volumetric assessment of glioblastoma resection. [61323] In our opinion, tumor volumes reported in the study of Senft are within the error limits of tumor volumetry. Further, a clear definition of “tumor” is one of the challenges to be solved besides improving accuracy of glioblastoma volumetry itself.…”
Section: Discussionsupporting
confidence: 64%
“…Further, we noticed that patient inclusion took significantly longer than expected based on a previous study. [6] This was mainly related to the indication for GTR as an inclusion criterion: Patients in which preoperatively was decided to leave a small area of contrast enhancement untouched because of the vicinity of eloquent areas or to avoid significant opening of the ventricular system, were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that semi-automatic segmentation methods have the potential to reduce the time required for segmentation (6)(7)(8). In addition, results from manual segmentation in HGG-resected patients have been reported to suffer from high interobserver variability (9). This is at odds with the need for stable imaging surrogate endpoints and prognostic markers in longitudinal prospective studies and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases the diagnosis of intracranial expansive lesion located in the region of the central sulcus of the brain was made by recording the nuclear magnetic resonances imaging (MRI). In 42.3% (11) findings of the lesions were localized in the left supratentorial hemisphere, and 57.7% (15) in the right supratentorial hemisphere. In order to achieve a clear preoperative orientation, especially in the present cases, infiltrative tumor growth, with no visible boundaries to the surrounding brain tumors, we performed to measure the distance of the central sulcus (the longest in the high parietal sulcus sections) in relation to the coronary suture on MRI …”
Section: Resultsmentioning
confidence: 96%
“…Therefore it is necessary to know the natural course of brain tumors in their initial, intermediary and terminal stage (30). Despite the maximum radical surgical resection and additional oncological protocols use combination of radio and chemotherapy, overall survival for patient with glioblastoma multiforme is between one and two years (17,15).The functions…”
Section: Introductionmentioning
confidence: 99%